MODEL PEMBELAJARAN BERBASIS PROYEK SEBAGAI MEDIA PENGUATAN KARAKTER - Halimah, Nur; Rahmawati, Aslihatul; Azhari, Ainul (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2025)
This research is motivated by the challenges of implementing effective character education, where traditional learning methods often fail to deeply instill values such as responsibility and cooperation. The focus of this study is to examine the effectiveness of the Project-Based Learning (PjBL) model as a medium for strengthening the character of responsibility, cooperation, and independence in junior high school students. As a crucial step, this study used a qualitative field research approach with 25 eighth-grade students at SMPN 1 Mauk. Data were collected through observation, interviews, and documentation of a project themed “Anti-Plastic Waste Campaign,” which was then analyzed using the Miles and Huberman model. The main findings indicate that the implementation of PjBL successfully encouraged positive character behavior changes. Students showed significant improvements in responsibility, active collaboration in groups, and independence in decision-making. In conclusion, the PjBL model has proven effective in shaping students' character through contextual and meaningful learning experiences, thus being recommended as a sustainable strategy for character education. ABSTRAKPenelitian ini dilatarbelakangi oleh tantangan implementasi pendidikan karakter yang efektif, di mana metode pembelajaran tradisional seringkali gagal menanamkan nilai-nilai seperti tanggung jawab dan kerja sama secara mendalam. Fokus penelitian ini adalah untuk mengkaji efektivitas model Pembelajaran Berbasis Proyek (Project-Based Learning/PjBL) sebagai media untuk penguatan karakter tanggung jawab, kerja sama, dan kemandirian pada siswa SMP. Sebagai langkah penting, penelitian ini menggunakan pendekatan kualitatif field research pada 25 siswa kelas VIII di SMPN 1 Mauk. Data dikumpulkan melalui observasi, wawancara, dan dokumentasi terhadap proyek bertema “Kampanye Anti Sampah Plastik,” yang kemudian dianalisis menggunakan model Miles dan Huberman. Temuan utama menunjukkan bahwa penerapan PjBL berhasil mendorong perubahan perilaku karakter yang positif. Siswa menunjukkan peningkatan signifikan dalam hal tanggung jawab, kolaborasi aktif dalam kelompok, dan kemandirian dalam pengambilan keputusan. Kesimpulannya, model PjBL terbukti efektif membentuk karakter siswa melalui pengalaman belajar yang kontekstual dan bermakna, sehingga direkomendasikan sebagai strategi berkelanjutan untuk pendidikan karakter.